Численное моделирование процесса холоднолистовой штамповки - Демина, Н. А.; Назарова, О. П.; Чепурной, А. Д.; Бараников, Я. Н. (НТУ "ХПИ", 2006)
Для моделювання операції пробивання листа в штампі створена спеціалізована система скінченно-елементного аналізу. На основі поєднання спеціалізованих програмних модулів, системи ANSYS, LS DYNA та параметричних моделей матриці, пуансона та заготовки створено програмно-модельний комплекс для вивчання процесу штамповки.

The specialized system of finite-element analysis is created for the modeling of operation of sheet punching in stamp. On the basis of combination of the specialized program modules, ANSYS and LS DYNA-systems and parametrical models of matrix, puncheon and billet the program and model complex is created for study of stamping process.
Keywords: напряженно-деформированное состояние; геометрическая нелинейность; контактное взаимодействие; механика разрушения